The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/cpp.2363
|View full text |Cite
|
Sign up to set email alerts
|

Early maladaptive schemas in patients with somatoform disorders and somatization

Abstract: Maladaptive schemas are stable relational patterns that develop through harmful childhood experiences with primary caregivers. Schemas within somatoform disorders are rarely explored even though these disorders are clinically important due to high prevalence, co-morbidity, and cost for the health care system. This study investigates schemas according to Young's schema theory in patients with somatoform disorders in comparison with healthy controls and patients with depressive or anxiety disorders. Further asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Despite the limited generalizability of case study evidence in the traditional sense, such comparative metasyntheses would allow for additional valuable clinical inferences and theory building. Samples of more homogenous case studies (e.g., stemming from mixed-methods randomized controlled trials) could provide further insight into the interpersonal dynamics of different clinical populations and allow for testing of more specific hypotheses on interpersonal dynamics-for example, from psychodynamic (Cornelis et al, 2017) or schema therapy domains (Henker et al, 2019).…”
Section: Conclusion and Suggestions For Research And Practicementioning
confidence: 99%
“…Despite the limited generalizability of case study evidence in the traditional sense, such comparative metasyntheses would allow for additional valuable clinical inferences and theory building. Samples of more homogenous case studies (e.g., stemming from mixed-methods randomized controlled trials) could provide further insight into the interpersonal dynamics of different clinical populations and allow for testing of more specific hypotheses on interpersonal dynamics-for example, from psychodynamic (Cornelis et al, 2017) or schema therapy domains (Henker et al, 2019).…”
Section: Conclusion and Suggestions For Research And Practicementioning
confidence: 99%
“…Our regression analysis results indicate that the emotional deprivation and vulnerability to harm schemas predict FIQ scores. In a recent study, overall higher scores were found on the schemas in somatization disorder, but the vulnerability to harm schema was reported to be related to somatization when depressive symptoms were controlled (16).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies draw attention to the relationships between schemas and pain disorders (14,15), somatization disorders (16), and migraine (17). However, as far as we know, there is only one study evaluating the relationship of EMS in fibromyalgia patients.…”
Section: Introductionmentioning
confidence: 99%
“…A total of eight studies (Ahmadpanah et al, 2017;Atalay, Atalay, & Bagdacicek, 2011;Chen, Tam, & Chang, 2019;Halvorsen et al, 2009;Henker et al, 2019;Wesley & Manjula, 2015) examined EMSs in depressed patients. The results of the meta-analyses showed the largest ESs for social isolation (g = 3.13, 95% CI [0.88, 5.38]), abandonment (g = 2.14, 95% CI [0.97, 3.31]), emotional deprivation (g = 2.12, 95% CI [1.00, 3.23]), defectiveness/shame (g = 2.11, 95% CI [0.49, 3.73]), and negativity/pessimism (g = 2.10, 95% CI [1.08, 3.12]) (Table 5).…”
Section: Depressionmentioning
confidence: 99%